1988
DOI: 10.1021/ef00012a010
|View full text |Cite
|
Sign up to set email alerts
|

Wettability measurements of coal using a modified Washburn technique

Abstract: trogen species. Although we cannot definitively separate the contributions of the PACN and soot to the yield of gtiseous nitrogen, the data suggest that, in the PAC conversion regime of our measurements, the net effect of the conversion of the nitrogen in PAC is the production of gaseous nitrogen species, most probably HCN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…The wetting properties of solid materials are of both fundamental and practical importance due to their wide range of applications such as detergency [1], liquid surface coating [2][3][4], flotation [5,6], chemical reactions at solid-liquid interface [7], agrochemicals, flows in reservoirs [8][9][10][11], and mass transfer in packed column [12]. Understanding and characterizing the wettability of solid surfaces are thus highly essential.…”
Section: Introductionmentioning
confidence: 99%
“…The wetting properties of solid materials are of both fundamental and practical importance due to their wide range of applications such as detergency [1], liquid surface coating [2][3][4], flotation [5,6], chemical reactions at solid-liquid interface [7], agrochemicals, flows in reservoirs [8][9][10][11], and mass transfer in packed column [12]. Understanding and characterizing the wettability of solid surfaces are thus highly essential.…”
Section: Introductionmentioning
confidence: 99%
“…Although core flooding methods rarely consider the effect of the coal heterogeneity in determination of relative permeability curves, other experimental studies using the sessile drop and captive bubble techniques have demonstrated that coal wettability is dependent on rank (Keller, 1987;Tampy et al, 1988), maceral composition (Arnold and Aplan, 1989;Ding, 2009;Fuerstenau et al, 1983;Ofori et al, 2010), mineralisation (Gosiewska et al, 2002;Susana et al, 2012) and the roughness (Drelich et al, 1996;Li et al, 2013). The sessile drop technique is convenient for the collection of contact angle data on a large number of coal samples, or sites on a sample, but there are limitations when coal wettability effects flow in cleats.…”
Section: Introductionmentioning
confidence: 99%
“…(ii) powdered/pulverised coal. These methods have included: film flotation (Fuerstenau et al, 1983;Hanning and Rutter, 1989;Polat et al, 2003), bubble-particle attachment (Nguyen et al, 1998;Ralston et al, 1999), penetration rate (Murata and Naka, 1983) and capillary rise (or Washburn method) (Tampy et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…For bulk coal surfaces these techniques include: captive bubble (illustrated in Figure 2.24) (Arnold and Aplan, 1989;Saghafi et al, 2014;Sakurovs and Lavrencic, 2011), tilted plate (Brady and Gauger, 1940;Yuan and Lee, 2013) and Sessile drop (Drelich et al, 2000;Gutierrez-Rodriguez et al, 1984). For coals that are in powder form, these methods have included: film flotation (Fuerstenau et al, 1983;Hanning and Rutter, 1989;Polat et al, 2003), bubble-particle attachment (Nguyen et al, 1998;Ralston et al, 1999;Ramesh and Somasundaran, 1990), penetration rate (Murata and Naka, 1983) and capillary rise (or Washburn method) (Tampy et al, 1988). (Saghafi et al, 2014).…”
Section: Techniques To Measure and Assess Wettabilitymentioning
confidence: 99%
“…Although core flooding methods rarely consider the effect of the coal heterogeneity in determination of relative permeability curves, other experimental studies using the Sessile drop and captive bubble techniques have demonstrated that coal wettability can be dependent on rank (Keller, 1987;Tampy et al, 1988), maceral composition (Arnold and Aplan, 1989;Ding, 2009;Fuerstenau et al, 1983;Ofori et al, 2010a), mineralisation (Gosiewska et al, 2002b;Susana et al, 2012) and the roughness of the coal surface (Drelich et al, 1996;.…”
Section: Introductionmentioning
confidence: 99%